Thermal comfort study in BPU7 lecture room - Muhamad Amir Syukri Mohamed (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this study is to perform simulation of airflow in lecture room using Computational fluid Dynamic (CFD) technique in order to obtain a condition what is in accordance to the thermal comfort requirement. This study involve the solveing the conservation of mass, momentum and energy are used to as a species transport.